2012
DOI: 10.1523/jneurosci.4703-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

TRPM2 Contributes to Inflammatory and Neuropathic Pain through the Aggravation of Pronociceptive Inflammatory Responses in Mice

Abstract: Accumulating evidence suggests that neuroimmune interactions contribute to pathological pain. Transient receptor potential melastatin 2 (TRPM2) is a nonselective Ca 2ϩ -permeable cation channel that acts as a sensor for reactive oxygen species. TRPM2 is expressed abundantly in immune cells and is important in inflammatory processes. The results of the present study show that TRPM2 plays a crucial role in inflammatory and neuropathic pain. While wild-type and TRPM2 knock-out mice showed no difference in their b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
159
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(168 citation statements)
references
References 58 publications
8
159
1
Order By: Relevance
“…Although not described in β-cells, a role for TRPM2 has been described in the inflammation through up-regulation of chemokines [42]. Inhibition of TRPM2 channels indeed prevents inflammation in a mouse model of colitis and inflammatory and neuropathic pain [42,43]. Thus TRPM2 channels could also contribute to MLDS-induced insulitis.…”
Section: Discussionmentioning
confidence: 99%
“…Although not described in β-cells, a role for TRPM2 has been described in the inflammation through up-regulation of chemokines [42]. Inhibition of TRPM2 channels indeed prevents inflammation in a mouse model of colitis and inflammatory and neuropathic pain [42,43]. Thus TRPM2 channels could also contribute to MLDS-induced insulitis.…”
Section: Discussionmentioning
confidence: 99%
“…29) TRPM2 is also involved in chemokine CXCL2 and NO production in cultured macrophages and microglia. 31,32) In line with these findings, TRPM2 regulates the migratory capacity of neutrophils and macrophages in response to ischemic brain injury, thereby secondarily perpetuating brain injury after the ischemic event. 43) Taken together, these results suggest that TRPM2 in microglia/macrophages could mainly contribute to the development of cerebral ischemic injury.…”
Section: Trpm2 Channels In Cerebrovascular Diseasementioning
confidence: 58%
“…30) Using cultured microglia derived from wild-type and TRPM2 knockout mice, Haraguchi et al showed that TRPM2 is involved in NO production. 31) Subsequently, Miyake et al examined the intracellular signaling mechanisms underlying these phenomena and demonstrated that combined application of lipopolysaccharide (LPS) and interferon-γ can stimulate TRPM2-mediated extracellular Ca 2+ influx in cultured microglia. 32) They also showed that activation of TRPM2 results in proline-rich tyrosine kinase 2 (Pyk2)-mediated activation of p38 mitogen-activated protein kinase and c-Jun N-terminal kinase (JNK) signaling, leading to the increased NO production in microglia.…”
Section: Physiological Roles Of Trpm Channels In Gliamentioning
confidence: 99%
See 2 more Smart Citations